Efisiensi persediaan bahan. Buku pegangan untuk perusahaan-perusahaan kecil dan menengah - AHYARI, AGUS (BPFE YOGYA, 1992)
Efisiensi persediaan bahan. Buku pegangan untuk perusahaan-perusahaan kecil ...